Agro-processing and horticultural exports from Africa - Emiko Fukase; Will Martin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Sub-Saharan African exports of horticultural and processed agricultural products are growing in line with the major shift towards these products in world markets. Continued growth in these exports may be vitally important for expanding returns from African agriculture and for increasing its overall exports. Policy reforms such as reductions in the tariff escalation facing Africa, improvements in the productivity of agricultural processing, and reductions in trade barriers within Africa and beyond would all further stimulate exports of processed agriculture. While essential, expansion of these exports should be regarded as complements to - rather than substitutes for - development of other dynamic export sectors.
Keywords: F13; F17; F63; Q17; 330; Africa; agro-processing; trade; horticulture